Theoretical Calculation of Different Ion Surface Interaction Parameters of Si Target - Ali, Sarwar H.; Saeed, S. R. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Longitudinal projected range, energy losses, and sputtering yield are calculated of silicon target that bombarded with inert ion gases such as He, Ne, Ar, Kr, and Xe using SRIM package. Obtained results show increasing of longitudinal projected range with ion energy and decreasing with incident ion mass. The energy losses originated by the nuclear and electronic depending on ion ranges, generally at low ion energy the nuclear stopping power is dominated in comparison with the electronic stopping power, and the range of domination varies with changing ion species. Further, the sputtering yield founded, increasing with ion energy up to maximum value then tending to decrease, as well as it increases with increasing ion incident angle and decreases with decreasing ion mass.
Keywords: sputtering ion range energy loss ion bombardement